Arabic-English code-switching in the academic discourse of Middle Eastern students - Anania, Syafila Husna (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
The phenomenon of bilingualism in academic settings is becoming increasingly common, particularly among students in the Middle East. In such contexts, switching between Arabic and English has become part of everyday communication practices, whether in class discussions, writing papers, or interactions among students. This study aims to identify the forms and functions of this bilingual usage within students’ academic discourse. A qualitative approach was employed, utilizing a semi-structured questionnaire distributed via Google Forms to three respondents currently pursuing their education in several Middle Eastern countries. Additionally, this research is supported by a literature review of various relevant scholarly sources. The results indicate that language switching occurs in various forms and serves multiple purposes, such as facilitating understanding of course material, explaining academic terminology, and adapting to the prevailing communication context. Thus, the alternating use of Arabic and English can be understood as a flexible and effective communication strategy in supporting the learning process and academic interactions.